Gearing Up for the Future of Manufacturing in Bangladesh - Gu, Yunfan; Nayyar, Gaurav; Sharma, Siddharth (World Bank, Washington, DC, 2021)
Labor-intensive, export-oriented manufacturing driven by the ready-made garments industry has transformed Bangladesh's economy. But with automation, changing trade patterns and servicification reducing the importance of wage costs globally, the creation of more sustainable jobs in the manufacturing sector now needs the upgradation of firms' capabilities and technology adoption. Drawing on the World Bank's "Bangladesh Firm-level Adoption of Technology Survey", this report shows that there is significant scope to improve the manufacturing sector's performance and future prospects by promoting the adoption of better technologies in firms. It discusses how Bangladesh can achieve this aim through policies that address informational barriers to the acquisition of capabilities in firms, leverage international connectivity for technology diffusion, and strengthen key markets and institutions that underpin firms investment in technology.